Evaluación de una dieta no convencional en lactantes del manatí amazónico Trichechus inunguis (natterer, 1883) criados en cautiverio, Iquitos – Perú - Guerrero Ushiñahua, Diana Thesalia (2024)
The present study was carried out in the facilities of the quarantine zone of the Amazon Rescue Center (CREA), located on the Iquitos – Nauta highway, km. 13.8, department of Loreto, with the objetive of evaluating four (2 mails and 2 females) lactanting amazonian manatees (Trichechus inunguis) of 8 to 12 months approximatly, recued and manteined in captivity, fed with a non – conventional diet with lactose free (substitude diary). Data of zootechnical indices, hematological profile, blood biochemestry, transit time, retention and digestive efficiency were collected from the offsprings under study. The investigation was quantitative, with a descriptive longitudinal non – experimental design and simple statistics were used to describe, comprehend and explain the objetives set. The manatees were fed 6 times a day with a diet based on lactose free milk (70%), proteic supplement (29.5%) and proapack premix micronutrients (0.50%) in every feeding, for a period of 50 days. The results show that the effect of the provided diet does influence in a positive way on the growth and development, demonstrating that the diet had a positive impact on the growth and development of the lactanting manatees and it did not negatively affect their health.